Crianças e jovens com medida de acolhimento residencial: a importância da arte e do desporto como estratégia de intervenção social: https://doi.org/10.53809/TS_ISS_2023_n.4_50-67 ("Temas Sociais" Journal, 2023)
This article aims to demonstrate the contribution of art and sport as a social intervention strategy with children and teenagers in residential care. Results obtained by the D'AR-TE project, an Innovation and Social Entrepreneurship Initiative, developed by the Casa de Acolhimento da Santa Casa da Misericórdia de Santarém, show a decrease in aggressive behavior and an increase in self-esteem in sixteen children and teenagers, after a year of attending sports (judo) and arts (theatre, music and body expression) workshops twice a week. By analyzing the affective and behavioral dynamics of children and teenagers, it is possible to perceive the effectiveness of these practices in promoting individual and social resilience and as a consequence the reduction of aggressive behavior, enabling individuals to have a health-ier psychic (re)organization and a redefinition of concepts and attitudes
Keywords: Residential Care; Social Intervention; Arts; Sports.